2021
DOI: 10.1038/s41598-021-92465-9
|View full text |Cite
|
Sign up to set email alerts
|

Blastocyst formation, embryo transfer and breed comparison in the first reported large scale cloning of camels

Abstract: Cloning, through somatic cell nuclear transfer (SCNT), has the potential for a large expansion of genetically favorable traits in a population in a relatively short term. In the present study we aimed to produce multiple cloned camels from racing, show and dairy exemplars. We compared several parameters including oocyte source, donor cell and breed differences, transfer methods, embryo formation and pregnancy rates and maintenance following SCNT. We successfully achieved 47 pregnancies, 28 births and 19 cloned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…The mean live birth rate ranges from 6.45% to 16.67% in different groups. This cloning efficiency is comparable to that using cell lines established using live normal tissues [25][26][27]. We have reported to our earlier study that fibroblast cell lines established from vitrified tissues showed similar growth patterns, apoptosis rate, and mitochondrial metabolism with cells from fresh tissues [39].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The mean live birth rate ranges from 6.45% to 16.67% in different groups. This cloning efficiency is comparable to that using cell lines established using live normal tissues [25][26][27]. We have reported to our earlier study that fibroblast cell lines established from vitrified tissues showed similar growth patterns, apoptosis rate, and mitochondrial metabolism with cells from fresh tissues [39].…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, we have demonstrated that healthy cloned offspring could be obtained by nuclear transfer using donor nuclei obtained from decade-old vitrified tissues of a suddenly deceased champion show camel named Mabrokan. Generally, tissue biopsy is taken ante-mortem and cell lines are established and cryopreserved at their early passage for future use as a nuclear donor in the SCNT program [ 25 , 26 , 27 ]. Here, we established a primary fibroblast cell line from deceased and vitrified dermal tissues and produced 11 viable offspring from those somatic cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A photograph of the transferred embryo is presented in Figure 1 . We have followed our standard laboratory procedure for collection of tissue from somatic cell donors, the establishment of fibroblast cell line, super stimulation of oocyte donor, synchronization of oocyte donor and recipient camels, embryo transfer, and pregnancy diagnosis ( 7 9 ). Pregnancy was confirmed 50 days after embryo transfer by ultrasonography ( Figure 2 ).…”
Section: Case Presentationmentioning
confidence: 99%